2008
DOI: 10.1007/s10877-008-9110-7
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Airway Obstructions Using Photoplethysmography (PPG)

Abstract: The accuracy of this method shows promise for use in real-time monitoring situations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…In patients with obstructive sleep apnea, the size of these inspiratory swings in pulse transit time correlates well with the degree of inspiratory effort. 38 This lack of sensitivity is a major limitation in a clinical setting. 37 In a pilot study, a neural network signal analysis reached a sensitivity of 75% and specificity of 85% in detecting airway obstruction by PPG.…”
Section: Obstructive Apneamentioning
confidence: 99%
“…In patients with obstructive sleep apnea, the size of these inspiratory swings in pulse transit time correlates well with the degree of inspiratory effort. 38 This lack of sensitivity is a major limitation in a clinical setting. 37 In a pilot study, a neural network signal analysis reached a sensitivity of 75% and specificity of 85% in detecting airway obstruction by PPG.…”
Section: Obstructive Apneamentioning
confidence: 99%
“…Nonetheless, research efforts to apply machine learning algorithms in monitoring continued, and some applications have shown promise in pediatric anesthesia. Knorr and colleagues used a neural network to identify airway obstructions in postoperative patients based on photoplethysmography . A reliable, accurate application of this technology could have tremendous utility in postoperative pediatric patients, as the majority of critical pediatric airway events occur in the postanesthesia care unit .…”
Section: Machine Learning In Monitoring Of the Pediatric Airwaymentioning
confidence: 99%
“…In a pilot study using neural network signal analysis, airway obstruction was identified by PPG-derived signals (Nonin Medical, USA) in a sample of extubated surgical patients prior to PACU arrival (75% sensitivity and 91% specificity) (45). When AHI > 68%, Romem et al found that PPG demonstrated 70% sensitivity and 91% specificity compared to PSG (46).…”
Section: Ppg-derived Signal For Rrmentioning
confidence: 99%
“…At present, there are several studies about PPG for the evaluation of sleep apnea (4850). However, there are limited reports of PPG as the special monitoring tool for postoperative OSA patients, although RR is regarded as a clinically important parameter for monitoring the respiratory condition (45, 51). …”
Section: Ppg-derived Signal For Rrmentioning
confidence: 99%